Analisa Kebijakan Pemerintah Terkait Ancaman Pengangguran Pasca Kenaiakaninflasi Di Kota Banten - Michelle Go 6), Hery Haryanto1) Angel 2), Frendy 3), Janes 4), Jolin 5), (Bata Ilyas Educational Management Review, 2022)
Inflation and unemployment, these two things will of course be interrelated which is one of the problems experienced by almost everyone in the world. One of them is Indonesia in the province of Banten which has a total population of 13.16 million people (1,248 people/km²) which ranks third in Indonesia with the largest population.That being said it became the objects of analysis, that is related to the threat of unemployment caused by inflation. And to calculate and the impact of inflation has on unemployment and steps that taken by the government.